Analisis Feature dan Machine Learning Untuk Pencarian Web - Anggun Cipta (Jurnal Sistem Cerdas, 2018)
The use of website socialization is increasingly still for that amount of information growing rapidly, the harder it is to find the information within the specified time. The main searches for searches that are irrelevant or incompatible with user preferences, keyword-based searches, short questions. In this paper, we will examine the various features used in information retrieval. We will also discuss the relevance of web pages with users. We have classified by feature. In the end, we will compare different techniques and their pros and cons are discussed.